Characterization of graphene reinforced Al-Sn nanocomposite produced by mechanical alloying and vacuum hot pressing. (2018) - Sethuram, D.; Koppad, Praveennath G.; Shetty, Harshavardhan; Alipour, Mohammad; Kord, S.
Abstract: In the present work, graphene (Gr) reinforced Al-Sn matrix nanocomposites were prepared by ball milling and vacuum hot pressing. The powder morphologies of Al-Sn and graphene during different intervals (2, 4, 8 & 12 hours) of time were studied using Scanning Electron Microscope (SEM) and Energy Dispersive Spectroscopy (EDS). Further the 12 hours ball milled nanocomposite powders were subjected to vacuum hot pressing at a temperature and pressure of 540°C and 40 MPa respectively. The size of Al-Sn/Gr powders decreased with the increasing in milling time due to fracturing of big particles. The graphene was seen on the surface at the initial hours of ball milling but found to disappear in the Al-Sn powders at end of 12 hours of ball milling. The presence of high weight fraction of graphene in Al-Sn matrix grain boundaries made sintering process difficult leading slight drop in experimental density values when compared to that of theoretical density. However, the addition of 1 and 2 wt% graphene to Al-Sn showed about 27 and 48% increase in the microhardness values respectively.